EFFECT OF ADDING WOOD HUSH ASH ON HIGH PLASTICITY CLAY AGAINST SWELLING VALUE - Soewignjo Agus Nugroho; Ferry Fatnanta; Agus Ika Putra (Jurnal Infrastruktur, 2023)
This research is against the background of the large amount of sawdust waste that is not used so that it has the potential to become B3 waste (leakage) due to decomposition. The use of ash from waste incineration such as RHA (rice hush ash), FABA (fly ash, bottom ash) has proven successful in increasing the carrying capacity of clay soils. The combination of ash and cement additives or/and lime, for some cases, also manages to increase the shear strength of the soil. The study aims to utilize sawdust waste ash, WHA (wood hush ash) mixed with cement and/or lime for the stabilization of high plasticity clay. The research method focused on changes in swelling potential and changes in swelling pressure due to the addition of WHA. Several variations of the mixture are made to be able to conclude the best composition of the mixture from these additive ingredients. Sample testing using a Konsolidometer (Oedometer) test kit and swelling measurements by overloading the sample by 1.0 to 5.0 kPa. Samples are printed by compacting using a standard proctor by adding water according to the OMC value of the original soil. The mixture is tested without being muffled and pre-soaked. The swelling test results showed that there was a change in soil type from high plasticity clay (CH) to high plasticity silt (MH). The addition of cement, lime, WHA or a mixture of 2-3 additives is proven to reduce the potential for expansion. The addition of a mixture of additives by 10% reduces the swelling potential to a medium. The addition of lime 10% lowers the swelling potential to Low, while the addition of cement or lime, or WHA of less than 5% does not change the potential to expand the soil. The mixture that best lowers the level of soil development consists of 90% cement soil (95% Clay+5% Cement), 6% lime, and 4% WHA.